2018
DOI: 10.1002/cne.24493
|View full text |Cite
|
Sign up to set email alerts
|

Retinal photoreceptor and ganglion cell types and topographies in the red fox (Vulpes vulpes) and Arctic fox(Vulpes lagopus)

Abstract: The red fox (Vulpes vulpes) is the carnivore with the widest distribution in the world. Not much is known about the visual system of these predominantly forest-dwelling animals. The closely related Arctic fox (Vulpes lagopus) lives in more open tundra habitats. In search for corresponding adaptations, we examined the photoreceptors and retinal ganglion cells (RGCs), using opsin immunohistochemistry, lucifer yellow injections and Nissl staining. Both species possess a majority of middle-to-longwave-sensitive (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 105 publications
(222 reference statements)
0
5
0
2
Order By: Relevance
“…However, one study found that rabbits, guinea pigs, and mice had both L/M and S cone opsins expressed in what are called transition cones or those found between the L/M cone dense superior retina and the S cone dense inferior retina of these species (Rohlich, van Veen, & Szel, 1994). A later study found co‐expression of S and L/M cone opsins in all the cones found in the retina of the Siberian hamster ( Phodopus sungorus ) and pouched mouse ( Saccostomus campestris ) (Lukats et al, 2002) and a third study found similar faint expression of L/M cone opsins in all S cones in the retinas of the red fox ( Vulpes vulpes ) and Artic fox ( Vulpes lagopus ) (Malkemper & Peichl, 2018). There is further evidence of co‐expression in insectivores (Peichl, Kunzle, & Vogel, 2000), salamanders (Isayama et al, 2014), and even humans (Xiao & Hendrickson, 2000) in different regions of the retina, but it is still unknown how common this phenomenon is in other animal groups, such as the order Carnivora.…”
Section: Discussionmentioning
confidence: 94%
“…However, one study found that rabbits, guinea pigs, and mice had both L/M and S cone opsins expressed in what are called transition cones or those found between the L/M cone dense superior retina and the S cone dense inferior retina of these species (Rohlich, van Veen, & Szel, 1994). A later study found co‐expression of S and L/M cone opsins in all the cones found in the retina of the Siberian hamster ( Phodopus sungorus ) and pouched mouse ( Saccostomus campestris ) (Lukats et al, 2002) and a third study found similar faint expression of L/M cone opsins in all S cones in the retinas of the red fox ( Vulpes vulpes ) and Artic fox ( Vulpes lagopus ) (Malkemper & Peichl, 2018). There is further evidence of co‐expression in insectivores (Peichl, Kunzle, & Vogel, 2000), salamanders (Isayama et al, 2014), and even humans (Xiao & Hendrickson, 2000) in different regions of the retina, but it is still unknown how common this phenomenon is in other animal groups, such as the order Carnivora.…”
Section: Discussionmentioning
confidence: 94%
“…In our Asiatic black bear, the retinal photoreceptor layers consisted of rods and cones, as was seen in the brown bear Ursus arctos horribilis , diurnal and nocturnal Canidae, and Mustelidae [ 23 , 26 , 68 , 70 , 83 , 114 ]. Research by Peichl et al, 2005 [ 27 ], and Heyward et al, 2020 [ 23 ], on the American black bear, brown bear and the polar bear showed the presence in retinal photoreceptor L-cones and S-cones in the brown bear and polar bear, and long/medium (L/M) wavelength sensitive L/M-cones and S-cones in the American black bear, suggesting that the bears have the potential for dichromatic color vision with high acuity, similar to the red fox and Arctic fox, which possess a majority of middle-to-longwave-sensitive (M/L) and a minority of shortwave-sensitive (S) cones, indicating dichromatic color vision [ 115 ]. The polar bear, which is overall well adapted to its semiaquatic lifestyle and its rather colorless habitat of snow and ice, has also retained both cone opsins and points to different visual demands and adaptive pressures on polar bears and seals.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Review of the morphological analysis of orbital region, eye tunics, eyelids and orbital glands of the Caniformia suborder [ 23 , 24 , 25 , 26 , 28 , 29 , 30 , 31 , 66 , 67 , 68 , 69 , 72 , 75 , 76 , 83 , 84 , 85 , 86 , 87 , 89 , 91 , 92 , 96 , 97 , 103 , 104 , 106 , 107 , 111 , 113 , 115 , 116 , 117 , 118 , 119 , 121 , 122 , 127 , 130 , 131 , 132 , 135 , 138 , 139 , 143 , 150 , 151 , 152 , 158 , 163 , 164 ,…”
mentioning
confidence: 99%
“…Therefore, we estimated the SRP of Bryde's whale and the humpback whale in air by multiplying the estimates of SRP in water by 0.75 (the ratio of the refractive index of air to the aqueous and vitreous humours) [Hanke et al, 2009;Coimbra et al, 2012]. The estimates of SRP that we present should be considered as theoretical upper limits [Pettigrew et al, 1988;Collin and Pettigrew, 1989] because it is likely that not all of the RGCs in the area of peak density are all involved in resolution tasks [Hughes, 1977;Wässle, 2004;Malkemper and Peichl, 2018]. Nevertheless, in mammals, including cetaceans, anatomical estimates of SRP are in close accordance with behaviourally derived measures [Pettigrew et al, 1988;Pettigrew and Manger, 2008].…”
Section: Spatial Resolving Powermentioning
confidence: 99%